Cooperation among community leaders: The role of women’s leadership and exposure to conflict - Nigus, Halefom Yigzaw; Abay, Kibrom A. (International Food Policy Research Institute, 2024)
In rural settings, community leaders play important roles in mobilizing resources and delivering public goods and services. However, little is known about their attributes and incentives in delivering these public goods and services. Exploiting survey, lab-in-the-field experiment, and geo-referenced data, we study the role of leaders, especially women’s leadership, and their exposure to conflict in explaining differences in cooperation among com-munity leaders in Ethiopia. We measure cooperation through a public-good experiment and examine the implications of community leaders’ characteristics. We then merge these lab-in-the field experimental data with geo-referenced data on conflict exposure to examine the implication of different types of conflict on community leaders’ cooperation behavior. We find that female leaders contribute more to public goods than their male counterparts. For example, compared to those assuming the highest official administrative responsibility in the village, women leaders contribute about 11 percent more to the public good. We also document nuanced findings that reconcile existing mixed evidence on the implication of exposure to conflict on cooperation: while conflict events that affect the whole community, such as political violence (including battles) are associated with higher cooperation, other types of conflict (e.g., demonstrations and riots) are associated with lower levels of cooperation. Finally, we identify additional predictors of cooperation among community leaders, including beliefs about other leaders’ cooperative behavior. These findings shed light on potential avenues for facilitating and fostering cooperation among community leaders.